PENGARUH EARNING PER SHARE DAN PRICE EARNING RATIO TERHADAP HARGA SAHAM PADA PT BANK CENTRAL ASIA Tbk PERIODE 2012-2022 - Satria, Rita; Sukmana, Sri Rahmawati; Herlianti, Elva; Nufzatutsaniah, Nufzatutsaniah (Jurnal Riset Akuntansi Politala, 2024)
This research aims to determine the influence of Earnings per Share (EPS) and Price Earning Ratio (PER) on Stock Prices at PT Bank Central Asia Tbk for the period 2012-2022. The research method employed is quantitative research with an associative type, and the population of the study comprises the financial reports of PT Bank Central Asia Tbk for the period 2012-2022. The data sample is derived from the Income Statement, Notes to the Financial Statements, and Summary of Stock PT Bank Central Asia Tbk for the period 2012-2022. Data analysis is conducted using SPSS Version 25, and the data testing includes Descriptive Statistical Test, Classical Assumption Test, Multiple Linear Regression Test, Correlation and Determination Coefficient Test, Partial Hypothesis Test (t-test), and Simultaneous Hypothesis Test (F-test). The results of the t-test in this study indicate that the Earnings per Share variable has a significant influence on Stock Prices, while the Price Earning Ratio variable also significantly affects Stock Prices. Meanwhile, the F-test results show that both the Earnings per Share and Price Earning Ratio variables simultaneously have a significant influence on Stock Prices, with a determination coefficient of 98.6%, indicating a strong relationship.